HIV risk behaviours differ by workplace stability among Mexican female sex workers with truck driver clientele - Nadine E. Chen; Steffanie A. Strathdee; Gudelia Rangel; Thomas L Patterson; Felipe J. Uribe-Salas; Perth Rosen; Jorge Villalobos; Kimberly C. Brouwer (SAGE Publishing, 2012)
Background. In a study of female sex workers (FSWs) servicing truck driver clients in Mexican border cities, we evaluated differences in HIV/STI risk behaviours determined by workplace. Design and Methods. Our study was cross-sectional and its population comprised 100 FSWs from Nuevo Laredo (US border) and 100 FSWs from Ciudad Hidalgo (Guatemalan border). The main outcome was that the primary place of sex work was unstable in a public place (street, vehicle, gas station, etc.) intead of stable (bar, brothel, and hotel). Logistic regression was used to identify correlates associated with trading sex at unstable workplaces in the last month. Results. Of the FSWs surveyed, 18% reported an unstable workplace. The majority of FSWs surveyed were young (<30 years), single, had <9th grade education, and had worked in the sex trade for a median of 4.9 years. After controlling for study site, FSWs with unstable vs stable workplaces were more likely to have a majority/all truck driver clientele, but were less likely to have visited a gynaecologist in the last year (OR 0.1, 95% CI 0.03-0.4) or ever had an HIV test (OR 0.1, 95% CI 0.06-0.3), and there was a trend towards lower condom use self-efficacy scores (OR 0.8 per unit increase, 95% CI 0.7-1.0). On multivariate regression, unstable workplace was associated with having majority/all truck driver clientele, being surveyed in Nuevo Laredo, and decreased odds of ever having an HIV test. Conclusions. Among Mexican FSWs with truck driver clients, providing safe indoor spaces for sex work may help facilitate public health interventions that improve HIV/STI prevention and reproductive health outcomes.